Microstructural evolution and mechanical performance of Ni-modified sand-cast excavator bucket teeth - Ery Hidayat; Ari Siswanto; Gita Novian Hermana; Roni Kusnowo; Cecep Ruskandi; Sophiadi Gunara; Asep Indra Komara (Jurnal Polimesin, 2026)
Excavator bucket teeth require high strength, hardness, and impact toughness to withstand severe service conditions involving abrasion and repeated impact. Achieving this combination of properties in sand-cast low-alloy steels remains challenging. This study investigates the microstructural evolution and mechanical properties of nickel-modified sand-cast bucket teeth subjected to a five-step heat treatment process. The material was produced by sand casting with the addition of 0.6 wt.% Ni, followed by sequential heat treatment consisting of normalizing, pre-tempering, quenching, and double tempering. Microstructural characterization and mechanical testing were conducted to evaluate the effects of the heat-treatment sequence on material performance. The applied heat treatment produced a lath martensite as the dominant microstructure with the presence of retained austenite. After the final tempering stage, the tensile strength reached 1206 MPa, with a hardness of 51 HRC, and an impact toughness of 26.1 J/mm2. The improved impact resistance is associated with retained austenite promoted by nickel addition. Fractographic analysis revealed predominantly ductile fracture characterized by dimple formation, followed by crack propagation involving intergranular and secondary cracking features. These results demonstrate that nickel modification combined with heat treatment effectively improves the mechanical performance of sand-cast bucket teeth.